ANALISIS FUNGSI MITOS KURI DAN PASAI BAGI MASYARAKAT ASLI TELUK WONDAMA - Suabey, Rinetha Stella (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2017)
This paper aims to describe the function of Kuri and Pasai myths for the native people of Wondama Bay. The mythical function itself as part of oral literature aims to enrich the understanding of the indigenous people of Wondama Bay about its oral literature. Myths Kuri and Pasai is the cultural result of the people of Wondama Bay which continues to be passed down from generation to generation. In the function of the Myth of Kuri and Pasai there are three functions, among others: 1) aesthetic function, in the aesthetic function there are two functions such as the function of the symbol and didactic function, 2) the function religiou, 3) the social function.